UNSUR-UNSUR KESASTRAAN DALAM PUISI NAHJ AL-BURDAH KARYA ’ABD AL-ḤAMĪD IBN AḤMAD AL-KHAṬĪB - Rosalinda, Rosalinda; Nurdin, Nurdin (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
This article examines Nahj al-Burdah, a work by the Saudi Arabian poet 'Abd al-Ḥamīd ibn Aḥmad al-Khaṭīb (d. 1381 H). This article aims to discuss the literary aspects based on Ahmad Amin's concept. This concept includes analysis of emotions, meaning, imagination, and stylistics. According to Amin, the stylistics includes aspects of rhythm and rhyme. The analysis results show that this madḥ al-Nabī work has a distinctive characteristic: expressing love for Allah SWT before expressing love for Prophet Muhammad Saw. This madḥ of the Prophet contains eleven themes, including the poet's nostalgia, good news for the soul, repentance, surrender, and hope, praise for the Prophet, the birth of the Prophet, the miracles of the Prophet, the glory of the Qur'an, struggles in jihad, the Isrā' and Mi'rāj, seeking forgiveness from Allah, and al-munājāh. The emotional expressions of love in the poem include feelings of love, fear, regret, satisfaction, and submission to Allah SWT. The imagination that emerges in this poem focuses on visualizing the depiction of angels delivering revelation to the Prophet. The language style used by the poet includes tasybīh, majāz, and kināyah. The poet chooses the rhythm of baḥr basīṭ and the rhyme of mīm.